Family Ties and Urban–Rural Linkages among Older Migrants in Nairobi Informal Settlements. Issue 3 (29th March 2012) - Mberu, Blessing Uchenna; Ezeh, Alex Chika; Chepngeno‐Langat, Gloria; Kimani, James; Oti, Samuel; Beguy, Donatien
ABSTRACT Building on African migration as a household survival strategy; urban–rural linkages as critical for migrants' continued engagement with origin communities; reintegration in case of return; and safety net for supplementing precarious urban incomes; we examine the role of family ties in rural origin linkages among 1, 693 older migrants living in Nairobi informal settlements. Despite the grim of slum residence, 80% of older migrants in Nairobi slums maintained contact with their rural origin homes during a full year of observation. Family‐related factors, especially members of the nuclear family residing in rural origin, explained 45% of explained linkages. Religion, ethnicity, land ownership at origin, and current health and economic statuses are other key predictors. The patterns and reasons of linkages are consistent with migrants' positive contributions to the upkeep of rural origin households. Our findings are well‐anchored in the larger continental literature that has shown the urban migrant as not a 'disembedded individual' but instead part of rural origin collectives. Against the weakness of state safety net system, the study sheds crucial light on the enduring importance of sociocultural networks in people's everyday lives, particularly the importance of family ties for older migrants. To the extent that poor health status, being aged 60 years or older, and long duration of residence in the slums, which are predictors of low propensities to maintain contacts with rural origin, are also indicators of diminished social engagement, policy interventions among the urban poor may need to include efforts to enhance rural origin reintegration of the most‐aged individuals. Copyright © 2012 John Wiley & Sons, Ltd.